Evaluation of the Job Training Policy Implementation Process at the Manado City Manpower Office in IT Perspective - Pulukadang, Raisha A.M.; Langkai, Jeane E.; Tumbel, Goinpeace H. (International Journal of Information Technology and Education, 2023)
Implementation of training programs Work based on the Minister of Manpower Regulation Number 11 of 2013 concerning Guidelines Maintenance System Training National Work. Implementation of training programs carried out by the Manado City Employment Service experienced several obstacles, such as unemployment data on the same with existing real data. Study This uses the theory implementation of public policy. Objective study This is to know How the implementation of training programs is suitable to work with the needed company at the Manado City Employment Service. Study This use method studies qualitative descriptive. Data was obtained through observations, interviews, as well as documentation. Research results This discloses that evaluation of implementation programs policy training Work at the Manado City Employment Service is feasible next However with several repairs like providing more facilities sufficient to do so complete lack of maintenance training, adding source Power teacher or instructor Training for implementation training can walk in a way maximum, as well increase Work The same with companies related for help absorption of alumni participants training to the world Work.